1983
DOI: 10.1111/j.1432-1033.1983.tb07293.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Two Different Types of Pyridine Nucleotide Transhydrogenase Found in Living Organisms?

Abstract: Two types of pyridine nucleotide transhydrogenases have been reported in living organisms. The energylinked transhydrogenase is found in mitochondria and in certain heterotrophic and photosynthesizing bacteria, while the non-energy-linkcd transhydrogenase is found in certain heterotrophic bacteria. The presence of a structurally similar non-energy-linked transhydrogenase in A-otohacter vinelandii, Pseudomonas aeruginosa and Pseudomoizas fluorescen.r is readily shown in extrach Tram these bacteria with Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0
2

Year Published

1985
1985
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 30 publications
3
32
0
2
Order By: Relevance
“…At this time we can not exclude the possibility that NADPH could also be oxidized by complex I or that a transhydrogenase could shuffle the electrons from NADPH to NAD 1 before the transfer to complex I. Such a transhydrogenase was found for instance in Pseudomonas fluorescens [19] and also in other organisms [20].…”
Section: Discussionmentioning
confidence: 99%
“…At this time we can not exclude the possibility that NADPH could also be oxidized by complex I or that a transhydrogenase could shuffle the electrons from NADPH to NAD 1 before the transfer to complex I. Such a transhydrogenase was found for instance in Pseudomonas fluorescens [19] and also in other organisms [20].…”
Section: Discussionmentioning
confidence: 99%
“…bacteria [117]. Thanks to the proton gradient generated across both the mitochondrial inner membrane and the cell membrane of bacteria, the apparent equilibrium constant of the system is changed, causing a shift towards the production of NADPH and NAD + [118].…”
Section: Ec 151: Oxidoreductases Of Chenh Groupsmentioning
confidence: 99%
“…Both Liang and Houghton [6] and Voordouw et al [15] have suggested that a 94000-100000-M, protein is a component of the E. coli transhydrogenase. Prior to cloning the pnt gene, we attempted to purify the transhydrogenase of E. coli wild-type strain W6 using a method that involved stripping the membrane vesicles with urea, solubilizing the enzyme with deoxycholate in the presence of KCl, followed by ion-exchange chromatography and affinity chromatography using NAD linked to an agarose resin ( Table 2).…”
Section: Purification Of Transhydrogenase From E Coli Strain Jm83 P mentioning
confidence: 99%